An Interactive Preposition Game to Improve the Usage of Preposition of Place Among Grade 4 Students - Sultan Sultan; Ray Suryadi (Berumpun: International Journal of Social, Politics, and Humanities, 2022)
The purpose of this research was to enhance students' grasp of grammar, focusing particularly on prepositions of place, by utilizing the Interactive Preposition Game (IPG) as a method for teaching and learning.. The study involved fourth-grade students from an elementary school as participants, with the researcher who carried out the action research in the classroom also serving as the teacher. The intervention cycle was executed a single time. The gathered information consisted of tests, along with interviews, and the teacher's reflective journal. The data revealed progress, as evidenced by a rise in average scores from the second test (25%) to the first test (82%). Furthermore, it was discovered that the Interactive Preposition Game (IPG) was able to improve students' comprehension, motivation, and foster an enjoyable learning atmosphere within the classroom. The study's outcomes revealed that the students exhibited favorable behaviors and reactions when the Interactive Preposition Game (IPG) was employed as a tool for learning grammar.